Awareness about Knowledge, Attitude and Practice of Medical Ethics pertaining to Patient Care, among Male and Female Physicians Working in a Public Sector Hospital of Karachi, Pakistan - A Cross-Sectional Survey. Issue 1 (2018) - , Sabeena Jalal; , Muhammad Imran; , Ashar Mashood; Younis, Mustafa
No abstract available